Efek Peningkatan Serat Kasar Dengan Penggunaan Daun Murbei Dalam Ransum Broiler Terhadap Persentase Bobot Saluran Pencernaan. (Effects Fiber Improved by Using Mulberry Leaf in the Broiler Diet Against Gastrointestinal Weight Percentage) - Has, Hamdan (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2014)
This study conducted to determine the effect of increasing crude fiber by using murlberry leaf on weight percentage of broiler digestive tract. One hundred DOC (day old chick) broilers, mulberry leaf, rumen fluid and other feed ingredients used in a completely randomized design research with 5 treatment T0 (control), T1 (10% mulberry leaves), T2 (10% fermented mulberry leaves), T3 (20% mulberry leaves) and T4 (20% fermented mulberry leaf) and 4 replications. Parameters observed was weight percentge of gastrointestinal tract (crop, proventriculus, gizzard, liver, pancreas, small intestine, cecum). The results showed the increasing crude fiber with 10% and 20% mulberry leaves (fermented and not fermented) were not significant (P> 0.05) on crop, proventiculus, liver and pancreas, but significant (P <0.05) increase gizzard weight at 20% murlberry compared to control, treatment 10% and 20% murlberry increase significantly (P <0.05) weight of the small intestine (doudenum, jejenum, ileum) and ceca compared control. Fermented and unfermented treatment showed no difference for all parameters. The increase in crude fiber diet can affect the digestive tract, especially the weight of gizzard, small intestine and cecum. Â  Keyword: Crude Fiber, Murlberry Leaf, Digestive Tract